TINJAUAN YURIDIS TENTANG TANGGUNG JAWAB KEMENTERIAN KESEHATAN TERHADAP KEBOCORAN DATA PRIBADI PADA APLIKASI PEDULILINDUNGI - Baskoro, Thomas Meidiansyah Tri (Tribuere, 2024)
This research is motivated by the emergence of the PeduliLindungi platform by the Government through the Ministry of Health, which functions as an integration of individual health data with health service facilities. However, this digitalization is faced with major challenges in the form of the risk of personal data leakage, which can harm users and violate their privacy. The description gives rise to the formulation of the problem How is the legal responsibility of the Ministry of Health for the leakage and use of personal data of PeduliLindungi consumers without permission based on Law No. 8 of 1999 concerning Consumer Protection Jo. Law No. 27 of 2022 concerning Personal Data Protection and What legal remedies can be taken by consumers who use PeduliLindungi for the leakage and use of personal data without permission from the Ministry of Health. The research uses a normative legal research method that explains the responsibilities of PeduliLindungi organizers based on the principle of responsibility and Law No. 8 of 1999 concerning Consumer Protection. The results of the study show the responsibility of the organizer based on the principle of responsibility due to fault (Fault Liability). Meanwhile, the legal remedies of the disputing parties, namely business actors and consumers, can be through the courts or BPSK.